Keterbukaan Informasi Publik dan Integritas Kepemimpinan Bangsa : Analisis Dokumen Laporan KKN, Skripsi dan Ijazah - Zainuddin T (Sadida Islamic Communications and Media Studies, 2026)
Public information disclosure is a fundamental principle in a democratic legal state that functions as an instrument of accountability, public supervision, and the formation of the integrity of the nation's leadership. Law Number 14 of 2008 concerning Public Information Disclosure (UU KIP) emphasizes that any information controlled by public bodies is basically open, while exceptions are only allowed on a limited basis through the consequence test mechanism. Normative legal research methods with legislative, conceptual, and case approaches, to analyze the position of academic documents in the public information disclosure regime and their implications for the integrity of leaders and compliance of state institutions. Data sources include related laws and regulations, decisions of the Information Commission and courts, as well as scientific literature on information disclosure, the state of law, and theories of open leadership and leadership with integrity. The analysis is carried out qualitatively through systematic legal interpretation and normative argumentation by placing the consequence test mechanism as a key instrument for restricting openness. The results of the study show that KKN reports, theses, and diplomas are not automatically included in information that is excluded according to Article 17 of the KIP Law and there are no provisions of laws and regulations in the higher education sector that explicitly classify diplomas as confidential information.